Breastfeeding experiences of call centre agents - Nkqayana, Siziphiwe (School of Management Studies, 2026)
Breastfeeding is one of the most effective strategies for improving infant nutrition and increasing child survival globally. Several experts consider breastfeeding to be the best way to feed a baby, as it provides numerous benefits to both the mother and the child. One of the main factors that contributes to the early weaning of breastfeeding infants in South Africa is the return to work. This study aimed to gain an in-depth understanding of the breastfeeding experiences of call centre agents when returning from maternity leave. This study employed a qualitative research method where seven semi-structured interviews were conducted with women who had a baby in the past two years and working in a call centre environment. Thematic analysis conducted on the data revealed three important themes: (1) Call Centre Policies and Feelings of Subordination Amongst Breastfeeding Women (2) Breastfeeding Support and Return to Work and (3) Call Centre Work Structure: Obstacles for Breastfeeding Moms. The study results revealed that the Covid-19 pandemic helped support breastfeeding because of the increased time at home as they were able to continue to breastfeed their babies while working from home, measures of trustworthiness and ethical considerations were adhered to throughout the study.